Peran Smartphone Terhadap Pertumbuhan Dan Perkembangan Anak - M. Gustian Sobry (Indonesian Institute for Counseling, Education and Therapy (IICET), 2017)
Smartphones can be used to be personal assistants, because these tools can store important data for business as well as be a reminder of what to do next by the user. Smartphones can input applications for chat, email, phone, social media, and entertainment. With the advancement of this technology also affect the pattern of child development. Currently almost all children in Indonesia have their own smartphone privately and it becomes a special task of parents to be able to monitor the use of smartphones for his baby. And here too the role of school counselors is very big in overcoming this